They Said We Were Brain Washed: How Thai Students Learn Democratic Values Under the Limited Socialization of Democratic Values.: The Case Study of the Thai Student Mob in 2020 - Kaewmano, Jaruwan (King Prajadhipok’s Institute Journal, 2024)
This article aims to understand the conditions that drive high school students in Thailand to protest the government in 2020, even though they are socialized with limited democracy under the Thai educational system. It uses qualitative research methods through documentary research and in-depth interviews with 70 high school students and 31 social-study teachers who were sampled from 24 schools that were involved in the political movement in 2020. This article uses content analysis along with discourse analysis and uses structuration theory to explain the findings. The study found that students can understand democratic values despite not being in a democratic environment under political socialization, which has limitations in dominating the thoughts and behaviour of the students. Meanwhile, students can consider and judge what to do under the limited socio-political structure. However, students cannot understand democratic values by evolution, instead by incidents that attack their former thoughts, which later leads to self-study of democratic values. The study found that democratic values learning would occur when three conditions come together: 1) changing of external structure, 2) enlightening of thought, and 3) an explanation that relates between the current situation and value of what the students hold in a way that could benefit them. However, the political values of the student can go back and forth like a cycle between enlightenment and compliance as the result of double learning due to the clash of ideas and practices of individuals under constraints of the structure.